Sikh Films (2001)
[Dt.:] Die Webseite Sikh Films stellt ein Projekt des panjabischen Fernsehschauspielers Mangal Dhillon vor, der Filme über den Sikhismus produzieren und diese - neben den gewöhnlichen Vorführungsstätten und dem Verkauf auch in panjabischen Dörfern vorführen lässt. Unter den Filmen finden sich sowohl Spiel- als auch Dokumentarfilme. - [Engl.:] This website provides information on project of the Punjabi TV-actor Mangal Dhillon who produces films on Sikhism and shows them - apart from the common venues in villages of Punjab. Amongst the films which are described on the website are documentaries as well as feature films